Seorang Wanita Lansia dengan Vertigo Perifer dan Neuralgia Trigeminal: Laporan Kasus - Fitriyani; Nikma Syalsabiela Fauzia (Medula, 2024)
Vertigo is a common complaint presenting frequently in primary care and emergency departments, which is a symptom of vestibular dysfunction and is described as a sensation of movement, most commonly rotational movements. Trigeminal neuralgia (TN) is defined as sudden, severe, brief, stabbing, electric shock-like and repetitive pain that is almost always unilateral in the distribution of one or more branches of the trigeminal nerve, which is highly disruptive and impacts basic human function. The analysis of this study is a case report of Mrs. N, 61 years old, came to the emergency room at Abdul Moloek Regional General Hospital with complaints of spinning dizziness as if the environment around him was spinning which occurred suddenly and pain on the left side of his face like a cut that had been getting worse since 1 day. Complaints of pain on the left side of the face spreading to the chin and left side of the neck have been felt for 2 years. On sensory examination of the Trigeminal Nerve, hyperalgesia and allodynia were found according to the left V1,2,3 dermatomes. The results of the patient's physical examination showed good hearing function, horizontal nystagmus (+), and Romberg's sign (+) balance test, heal to toe walking test (+), past pointing test (+). The patient's clinical diagnosis was vertigo and facial pain (neuralgia). Topis diagnosis, peripheral vestibular system and Trigeminal Nerve. Etiological diagnosis, peripheral vertigo and Trigeminal Neuralgia. The patient's management was infusion of Ringer's Lactate 20 drops/minute, Betahistine 2x24 mg, Omeprazole injection 40mg/12 hours, Carbamazepine 3x200 mg, Amitriptyline 1x25 mg, and Paracetamol 2x1000 mg fls. The prognosis for this patient is quo ad vitam dubia ad bonam, quo ad functionam dubia ad night and quo ad sanationam dubia ad bonam.